The Applications of Hyperspectral Imaging Technology for Agricultural Products Quality Analysis: A Review. Issue 2 (17th February 2023) - Wang, Bao; Sun, Jianfei; Xia, Lianming; Liu, Junjie; Wang, Zhenhe; Li, Pei; Guo, Yemin; Sun, Xia
ABSTRACT: With the improvement of people's living standard, the fast-increase demand for agricultural products with high quality is endless. Therefore, developing accurate and rapid detection methods for agricultural products quality analyses is of great importance and strongly required. Hyperspectral imaging (HSI) technology, as a rapid and non-destructive method, has earned wide concern. In this review, the applications of HSI for agricultural products quality analyses have been proposed to prove the feasibility of this technology for disease detection, grading, classification, detection of chemical attributes and other aspects. The application status of HSI in quality analyses for each category of agricultural products was summarized in several different aspects, including the quality properties, the used pattern, the modeling methods and the detection accuracy. Finally, based on the above summary, the advantages and disadvantages of HSI have been discussed and some viewpoints on current research situation and research directions of future have also been given.